Aortic Intramural Hematoma Presenting as Paraplegia Progressed into Segmental Aortic Dissection - Zhu, Hua-gang; Zha, Bin-shan; Liu, Bin (The Thoracic and Cardiovascular Surgeon, 2012)
Intramural hematoma (IMH) is a newly defined disease entity and the optimal management is still controversial as the disease shows varied clinical course. We present a case of type B IMH, initially presenting with paraplegia progressing to segmental aortic dissection (SAD) which the formed dissection displayed as a segmental distribution pattern. To our knowledge, it may become a new progression pattern of IMH progression. The SAD was successfully treated with both thoracic and abdominal endovascular aortic repair (TEVAR plus EVAR). In 1-year follow-up, the patient recovered almost completely with moderately neurological deficit and the blood pressure is in control.
Keywords: aortic intramural hematoma; paraplegia; natural history